Physical and mental health of nursing professionals in the post-pandemic world: integrative literature review (Research, Society and Development, 2022)
The aim of this study is to know the factors linked to the mental and physical alterations of nursing professionals in the post-pandemic COVID-19 pandemic. This is an Integrative Literature Review. Data collection occurred in April 2022, using the Databases of SCIELO and PUBMED, with the descriptors: COVID-19 AND Nursing AND Occupational Diseases. The inclusion criteria were studies between the years 2020 to 2022, the timeline is justified by the decree of the pandemic and pandemic peak in these years, randomized clinical studies or without randomization, qualitative and quantitative studies, experimental and almost experimental, available in full, according to the guide question, objective and descriptors used. The 7 articles used in the study showed that nursing professionals have remnants of pandemic apopice in both mental health and physical health. The alterations evidenced in the studies were: mental disorders such as anxiety, depression, Burnout syndrome, alopecia, rashes, gastric changes such as nerve gastritis and migraine attacks due to frontline experiences against SARS-COV-2, added to the scenario of lack of sufficient EPIS, high death rate, family absence and social isolation. Considering the consequences that occurred on the health and personal lives of professionals involved in the provision of care during the COVID-19 pandemic, strategies to cope with these sequelae are necessary, aiming to promote a better quality of life and overcome the moments experienced.